A new generalized AOR iterative method for solving linear systems - Nasabzadeh, Hamideh; Toutounian, F. (International Journal of Applied Mathematical Research, 2013)
In this paper, based on a block splitting of the coefficient matrix, we present a new generalized iterative method for solving the linear system Ax = b. This method is well-defined even when some elements on the diagonal of A are zero. Convergence analysis and comparison theorems of the proposed method are provided. Specially,the results shows that our new generalized AOR iterative method also, converges when A is an H-matrix. And for L-matrices, our new generalized Jacobi iterative method is faster than the classical Jacobi. The Numerical examples are also given to illustrate our results.